Latent profiles of emotion regulation strategies associated with alexithymia, nonsuicidal self‐injury and resilience among nursing students. (25th June 2021) - Mao, Cui; Lin, Mingjing; Shen, Shiyu; Li, Yuanyuan; Xie, Zihui; Li, Ping
Abstract: The present study sought to better understand the complex nature of emotion regulation in nursing students by exploring patterns of emotion regulation strategies (ERSs), and to examine the relationships between these unique profiles with alexithymia, nonsuicidal self‐injury (NSSI) and resilience. A total of 1960 nursing students ( M age = 19.56, SD = 1.13 years) were recruited. Using latent profile analysis, nursing students were classified into four profiles based on their ERS use: high reaction profile (HRP; 11.53%), medium reaction profile (MRP; 55.46%), adaptive reaction profile (ARP; 22.86%) and low reaction profile (LRP; 10.15%). This study found that relative to HRP and MRP, ARP and LRP showed a lower incidence of NSSI and alexithymia; HRP and ARP showed a higher level of resilience than MRP and LRP. Furthermore, LRP had the lowest level of resilience. This study highlights the importance of identifying the different ERS profiles among nursing students. Targeted programs are needed to enhance adaptive strategies and reduce maladaptive strategies to improve nursing students' psychological and behavioural performance.